A Comparative Study of Platelet Counts by Automated and Manual Method in Patients with Thrombocytopenia and Thrombocytosis - Pathak, Rakesh; Pudasaini, Sujata; Kharel, Manish; Kunwar, Saroj (Nepal Medical College Journal, 2025)
Platelet count is a vital parameter in the diagnosis and management of hematological disorders such as thrombocytopenia and thrombocytosis. Although automated hematology analyzers offer rapid and efficient platelet counting, their accuracy can be compromised in cases involving platelet clumping or morphological abnormalities, making manual methods still relevant for precise evaluation. This study aimed to evaluate the correlation and reliability of automated, Neubauer manual, and peripheral blood smear (PBS) methods for platelet counting. A hospital-based cross-sectional study was conducted over six months, including 321 patients undergoing platelet count testing, of whom 246 had thrombocytopenia and 75 had thrombocytosis. Platelet counts were measured using an automated hematology analyzer (Sysmex XN-550, Japan), Neubauer manual counting method, and PBS examination. Data were analyzed to compare and assess the correlation between the methods. The mean platelet count of thrombocytopenic cases across different methods were automated (79000± 33296/μl), manual (93900±40130/μl) and peripheral blood smear (91200±37560/μl), respectively. For thrombocytosis cases the mean platelet value across different methods were automated (597000±148000/μl), manual (590000± 164000/μl) and peripheral blood smear (601000±180000/μl), respectively. A strong correlation was observed among the methods (Neubauer manual vs automated, r=0.77, p=0.01 and Neubauer manual vs PBS r=0.78, p=0.01). There is no significant difference in platelet value between the methods. While all three methods exhibit strong agreement, the automated method may underreport platelet counts in thrombocytopenic samples. Neubauer manual and PBS methods remain valuable for confirming the low platelet counts.